Factors Affecting the Maintenance of Dental and Oral Health in Children of Elementary School of Harapan 1 Class 3 in Sumber Mulyo Rejo District Madya Binjai City - Ana Indrawati; Muhammad Badira; Imam Muhammad (Newinera Publisher, 2020)
This study aims to determine the factors that influence the maintenance of oral health in SD (Elementary School) Harapan 1 grade 3 children in Sumber Mulyo Rejo Village, Binjai Madya City in 2018. The design of this study was an analytical observational study with a cross sectional study type. The research was conducted in SD Harapan I grade 1 to grade 3 in Sumber Mulyo Rejo Village, Binjai Madya City in 2018. When the research was conducted in February-September 2018. The number of samples was 86 respondents and data collection used a questionnaire. Data analysis was performed using univariate, bivariate (chi square) and multivariate (multiple logistic regression prediction models). The results showed that the maintenance of dental and oral health in SD Harapan 1 grade 1 to grade 3 children in Sumber Mulyo Rejo Village, Binjai Madya City in 2018 was 75.6% not good. There is a significant relationship between student knowledge, student attitudes, diet, motivation to care for teeth, the UKGS program, and the attitudes of parents at SD Harapan I Binjai with the maintenance of dental and oral health for students at SD Harapan I Binjai in 2018. The conclusion of this study is that motivation to care for teeth is a factor that is most related to the maintenance of dental and oral health in SD Harapan 1 grade 1 to grade 3 children in Sumber Mulyo Rejo Village, Binjai Madya City, 2018. Promotional efforts are needed to increase students' knowledge about the importance of maintaining oral health such as posters on how to brush teeth true, good time brushing teeth, toothpaste used for brushing teeth and brushing teeth directly activities together at school.